What's the matter with Delaware? : how the first state has favored the rich, powerful, and criminal-and how it costs us all - Weitzman, Hal, 1972- (Princeton University Press, 2022)
"Delaware is so boring that it's funny, as immortalized by one of the most memorable jokes in the movie Wayne's World. Indeed, Delaware is the de facto capital of corporate America, the embodiment of blandness. But what if behind this banality lay a systematic enterprise that blatantly diverted public funds away from the poorest people in America and supported the worst criminals and dictators in the world? Legal scholars, financial journalists, and elite businesspeople will all tell you that by now it's common knowledge that Delaware is not just business friendly-it is an obvious financial haven for terrorists, criminals, dictators, arms-dealers, money-launderers, and tax evaders. But no one has put all the pieces together and written a book about it. Accomplished investigative journalist Hal Weitzman does just that. This book explains in clear terms to the broadest possible audience how Delaware diverts money from the poorest states in the US through various means, most obviously the "Delaware loophole," which in effect enables huge businesses such as Home Depot and WalMart to avoid paying state taxes to the states in which they actually conduct business. In Shut Down Delaware, Weitzman will also show how Delaware is an integral part of an international system that fosters extraordinary tax evasion and money laundering, through its indefensible system of incorporation, which allows anyone to set up a business without specifying who owns the business. Over time what this has led to is that some of the biggest and most well-known businesses in the world sharing the same Delaware addresses as the world's most notorious arms dealers and dictators. Using public data, interviews, investigative journalism, and academic scholarship, Weitzman will be the first to put the story together in book form and call the industry out. For years, US lawmakers and law enforcement have been criticizing foreign tax havens such as Switzerland and Luxembourg for unjust practices, but when the trail inevitably leads back to Delaware, there is nothing more they can say or do. Shut Down Delaware will bring this glaring discrepancy to light, and the implications could be tremendous. First, there is no defense for Delaware allowing business incorporation without any identification. Second, many states have gotten wise and passed legislation preventing businesses from taking advantage of the "Delaware loophole" but most, including the nation's poorest states, have not. A high-profile book could be just what it takes raise public awareness on both fronts, and if these laws were changed, a huge amount of business would be affected. Shut Down Delaware has the potential to create an enormous shift in the way the world's largest companies and shadiest illegal entities do business in the United States"--